2007
DOI: 10.1080/00365520701409035
|View full text |Cite
|
Sign up to set email alerts
|

Tissue levels of tumor necrosis factor-alpha correlates with grade of inflammation in untreated ulcerative colitis

Abstract: TNF-alpha is highly expressed in UC and correlates to the grade of inflammation. The sources of TNF-alpha were observed both in CD3+ lymphocytes and in macrophages. Cytokine expression (mRNA) profiles seem to be similar in patients with moderate to severe UC and CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
94
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(103 citation statements)
references
References 40 publications
7
94
2
Order By: Relevance
“…36,37 Total RNA was extracted from biopsies according to the Trizol method (Invitrogen, Paisley, UK) and quantified at 260 nm in a U-1500 UV/Vis spectrophotometer (Hitachi Instruments Inc, San Jose, CA). RNA integrity was assessed in an Agilent 2100 Bioanalyzer on RNA 6000 Nano chips (Agilent Technology, Bö blingen, Germany) according to the manufacturer's instructions and all samples included were found to be RIN Ն8 (RNA integrity number) on a scale from 0 to 10.…”
Section: Quantitative Pcr Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…36,37 Total RNA was extracted from biopsies according to the Trizol method (Invitrogen, Paisley, UK) and quantified at 260 nm in a U-1500 UV/Vis spectrophotometer (Hitachi Instruments Inc, San Jose, CA). RNA integrity was assessed in an Agilent 2100 Bioanalyzer on RNA 6000 Nano chips (Agilent Technology, Bö blingen, Germany) according to the manufacturer's instructions and all samples included were found to be RIN Ն8 (RNA integrity number) on a scale from 0 to 10.…”
Section: Quantitative Pcr Analysismentioning
confidence: 99%
“…The stability of ␤-actin as a housekeeping gene in the present context has been verified earlier. 36 Cytokine transcript levels relative to those of ␤-actin were analyzed according to the comparative C T -method and expressed as 2 Ϫ⌬CT ϫ 10E4. 39 The PCR efficiencies were close to 2 for both the IL-33 and the ␤-actin cDNA using serial dilutions of the templates.…”
Section: Quantitative Pcr Analysismentioning
confidence: 99%
“…Some reports have found positive correlations with the degree of disease activity in UC (Akazawa et al, 2002;Olsen et al, 2007) and CD (Olsen et al, 2007) but not in all for CD (Akazawa et al, 2002) and UC (Dionne et al, 1997). As far as we know no studies do exist on mucosal expressions of TNF-α and the prediction of the clinical course, whereas there are only few reports on the predictive value of mucosal TNF-α concentrations and the response to therapy.…”
Section: Proinflammatory Cytokines 421 Tnf-αmentioning
confidence: 99%
“…The reason for this difference between the two diseases is not known. Both CD patients and UC patients have increased levels of cytokines belonging to T-helper-1 response (Olsen et al, 2007;Vermeire et al, 2006). Santos et al investigated 957 subjects and found strong association between CRP and central abdominal obesity (Santos et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Dendritic cells (DCs) in UC show enhanced expression of TLR4, which is associated with microbial recognition, and these activated DCs induce production of proinflammatory cytokines (4). Intestinal tissue level of TNF-· is up-regulated in UC and correlates to the grade of inflammation (5). Colorectal cancer is one of the most serious complications of UC (6).…”
Section: Introductionmentioning
confidence: 99%